2017
DOI: 10.14814/phy2.13441
|View full text |Cite
|
Sign up to set email alerts
|

MiR-339 inhibits proliferation of pulmonary artery smooth muscle cell by targeting FGF signaling

Abstract: Pulmonary artery hypertension (PAH) is a fatal disorder. Recent studies suggest that microRNA (miRNA) plays an important role in regulating proliferation of pulmonary artery smooth muscle cells (PASMC), which underlies the pathology of PAH. However, the exact mechanism of action of miRNAs remains elusive. In this study, we found that miR‐339 was highly expressed in the cardiovascular system and was downregulated by a group of cytokines and growth factors, especially PDGF‐BB and FGF2. Functional analyses reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Furthermore, there is evidence that miRs target FGF signaling to regulate proliferation. In the study by Chen et al, the authors showed that miR-339 inhibited the proliferation of pulmonary artery smooth muscle cells (PASMCs) by targeting FGF signals [ 97 ]. By using EdU incorporation assay, they showed that miR-339 inhibited the proliferation of PASMC.…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frmentioning
confidence: 99%
“…Furthermore, there is evidence that miRs target FGF signaling to regulate proliferation. In the study by Chen et al, the authors showed that miR-339 inhibited the proliferation of pulmonary artery smooth muscle cells (PASMCs) by targeting FGF signals [ 97 ]. By using EdU incorporation assay, they showed that miR-339 inhibited the proliferation of PASMC.…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frmentioning
confidence: 99%
“…No studies have previously associated miR-339-3p with AAA. MiR-339 is highly expressed in the cardiovascular system and an important regulator of VSMC proliferation in pulmonary arteries [ 40 ]. Predicted genes targeted by miR-339-3p have been involved in adipocytokine, NOD-like receptor, chemokine, insulin, and MAPK signaling pathways and in apoptosis, all of them implicated in AAA pathology [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…При ишемической болезни сердца miR-339 способна увеличивать оксидативный стресс за счет подавления Nrf2/FOXO3 сигнального пути через специфический белок Sirt2 [24]. В исследовании J. Chen et al показано, что miR-339 подавляет пролиферацию гладкомышечных клеток легочной артерии через ингибирование FGF сигнального пути [25]. Результаты нашего исследования демонстрируют наличие значимо более высоких уровней экспрессии miR-27 и -339 у реципиентов сердца с развитием фибротических процессов в миокарде.…”
Section: результатыunclassified